Memahami Peran PendidikanTinggi terhadap Mobilitas Sosial di Indonesia - Arifin, Muhammad Husni (UI Scholars Hub, 2017)
This paper explains the connection between higher education and social mobility in Indonesia. Several theoretical frameworks as proposed by Raymond Boudon’s Inequality of Educational Opportunity (IEO) and Inequality of Social Opportunity (ISO) are relevant to explain the relation between the two variables. The result shows that the connection between higher education and social mobility is influenced by social-economic inequality, geographical factors, and cultural disparities. The decrease of inequality in the society allows more individuals to achieve higher education and attain upward social mobility.